2001
DOI: 10.1152/physrev.2001.81.4.1461
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Proteins and Cardiovascular Pathophysiology

Abstract: In the eukaryotic cell an intrinsic mechanism is present providing the ability to defend itself against external stressors from various sources. This defense mechanism probably evolved from the presence of a group of chaperones, playing a crucial role in governing proper protein assembly, folding, and transport. Upregulation of the synthesis of a number of these proteins upon environmental stress establishes a unique defense system to maintain cellular protein homeostasis and to ensure survival of the cell. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
282
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(300 citation statements)
references
References 426 publications
16
282
0
2
Order By: Relevance
“…Hsp72). The members of the HSP70 class bind to proteins in an energy-dependent (ATP) manner and help to maintain or restore the proper conformation of other proteins in the cell through a repetitive process of binding, bending, and release [Snoeckx et al, 2001]. They also play a role in keeping proteins unfolded until they reach their final destination in the cell or in trafficking irreversibly damaged proteins to lysosomes [Kiang and Tsokos, 1998].…”
Section: Mechanisms: Heat Shock Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hsp72). The members of the HSP70 class bind to proteins in an energy-dependent (ATP) manner and help to maintain or restore the proper conformation of other proteins in the cell through a repetitive process of binding, bending, and release [Snoeckx et al, 2001]. They also play a role in keeping proteins unfolded until they reach their final destination in the cell or in trafficking irreversibly damaged proteins to lysosomes [Kiang and Tsokos, 1998].…”
Section: Mechanisms: Heat Shock Proteinsmentioning
confidence: 99%
“…These bound complexes are very stable, which means that Hsp27 is able to bind to inactivated proteins and hold them in a recoverable state until normal physiological conditions are restored, and refolding can be performed by other chaperones such as Hsp70. Actin, in particular, has been found to be protected by the small HSPs [Snoeckx et al, 2001], which is important not only for the cytoskeleton of all cells, but also for the sarcomeres in cardiac tissue. In addition to preconditioning studies, which tend to induce a variety of protective stress proteins, transgenic studies in vitro [Martin et al, 1997;Brar et al, 1999;Vander Heide, 2001] have demonstrated that increasing levels of Hsp25/27 prior to simulated ischemia-reperfusion injuries can have a protective effect.…”
Section: Mechanisms: Heat Shock Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated post-ischemic expression of HSP27 may account for the reduced disruption of tubular epithelium cytoskeleton, attenuation of OS 24,37,38 , plus stabilizing of microfilaments, preventing protein dysfunction 39 and reducing ischemia induced membrane lipids degradation. [40][41][42] The lack of HSPs alongside degenerative lesions in the renal tubular epithelial cells may lead to electromechanical dissociation, resulting in acute renal failure. 43 …”
Section: Hsp27 and Acute Renal Failurementioning
confidence: 99%
“…The induction of Hsps is based on the nature of the toxic stimulus (Kalmar and Greensmith 2009). The selection of these Hsps in the present study was mainly based on their role in various xenobioticinduced cardiotoxic and cardiovascular disease models (Lin et al 2007;Snoeckx et al 2001). The expression profile of these Hsps is mainly used to monitor the cardiac pathophysiological consequences upon xenobiotic insults.…”
Section: Introductionmentioning
confidence: 99%